IMPLEMENTASI PROGRAM TAHFIDZUL QUR’AN DALAM MEMBENTUK KARAKTER RELIGIUS SISWA DI MAN SIDOARJO - Kharisma Syifanaya Firdausi (Universitas Islam Negeri Sumatera Utara Medan, 2026)
This study aims to analyze the implementation of the Tahfidzul Qur'an program in shaping the religious character of students at MAN Sidoarjo. This study uses a qualitative approach with a literature study type, namely reviewing various scientific sources in the form of journals, books, and relevant previous research. The results of the study indicate that the implementation of the Tahfidzul Qur'an program is carried out through memorization activities, muroja'ah, and structured evaluation. This program has been proven to be able to shape students' religious character such as discipline, responsibility, honesty, and steadfastness in worship. In addition, the success of the program is influenced by religious environmental factors, the role of teachers, and parental support. However, there are obstacles such as time constraints, differences in student abilities, and diverse learning motivations. Thus, the Tahfidzul Qur'an program is an effective strategy in strengthening students' religious character in the madrasah environment.